Synthesis by Microwaves of Bimetallic Nano-Rhodium-Palladium. (4th November 2013) - Ugalde, M.; Chavira, E.; Ochoa-Lara, M. T.; Figueroa, I. A.; Quintanar, C.; Tejeda, A.
Abstract : An improved acrylamide sol-gel technique using a microwave oven in order to synthesize bimetallic Rh-Pd particles is reported and discussed. The synthesis of Pd and Rh nanoparticles was carried out separately. The polymerization to form the gel of both Rh and Pd was carried out at 80°C under constant agitations. The method chosen to prepare the Rh and Pd xerogels involved the decomposition of both gels. The process begins by steadily increasing the temperature of the gel inside a microwave oven (from 80°C to 170°C). In order to eliminate the by-products generated during the sol-gel reaction, a heat treatment at a temperature of 1000°C for 2 h in inert atmosphere was carried out. After the heat treatment, the particle size increased from 50 nm to 200 nm, producing the bimetallic Rh-Pd clusters. It can be concluded that the reported microwave-assisted, sol-gel method was able to obtain nano-bimetallic Rh-Pd particles with an average size of 75 nm.